Penerapan Media Aplikasi Gambar Untuk Meningkatkan Kemampuan Membaca Pada Mata Kuliah Bahasa Inggris Matematika - Agus Qowiyudin; Amina Septia Sari; Lailatus Syarifah (JURNAL RISET RUMPUN MATEMATIKA DAN ILMU PENGETAHUAN ALAM, 2024)
The ability to use image applications with accuracy, fluency and good and correct understanding is a challenge for students in forming new knowledge. There are still many students who do not master the skills of taking pictures of their surroundings in the Arloopa Application. Therefore, this research aims to evaluate the application of image media techniques to the skill of taking pictures of surrounding objects. This research is descriptive qualitative research. This research was carried out in three cycles, each consisting of two face-to-face learning cycles. The data analysis techniques used were descriptive qualitative and quantitative analysis. The results of the research show that students in cycles I, II and III have average scores which indicate that the application of image media techniques can improve their ability to use image media applications. It was concluded that the application of effective image media can increase the ability to take pictures of surrounding objects so that they become spatial shapes. Image media can facilitate students in learning English Mathematics.